COMPETENT APPROACH IN THE EDUCATIONAL PROCESS (European Journal of Interdisciplinary Research and Development, 2023)
This article analyzes the term competence, its origin and importance in the educational process. Also, are given comments on the scientific research of foreign researchers regarding competence.